2019
DOI: 10.1073/pnas.1818573116
|View full text |Cite
|
Sign up to set email alerts
|

Molecular engineering of an efficient four-domain DAF-MCP chimera reveals the presence of functional modularity in RCA proteins

Abstract: The complement system is highly efficient in targeting pathogens, but lack of its apposite regulation results in host-cell damage, which is linked to diseases. Thus, complement activation is tightly regulated by a series of proteins, which primarily belong to the regulators of complement activation (RCA) family. Structurally, these proteins are composed of repeating complement control protein (CCP) domains where two to four successive domains contribute to the regulatory functions termed decay-accelerating act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 36 publications
0
9
0
2
Order By: Relevance
“…A similar conclusion was also drawn following the functional analyses of domain swap mutants of VCP and Kaposica, wherein individual domains of these viral regulators were swapped with the homologous domains of DAF or MCP [121,123]. A recent study on DAF and MCP chimera showed that domains 1-2 (homologous domains in DAF are CCP 2-3) and 2-3 also serve as functional modules for DAA and CFA in these proteins [125]. It can, therefore, be concluded that vRCAs are true homologs of huRCA proteins.…”
Section: Structure-function Relationship Of Viral Rcamentioning
confidence: 69%
See 4 more Smart Citations
“…A similar conclusion was also drawn following the functional analyses of domain swap mutants of VCP and Kaposica, wherein individual domains of these viral regulators were swapped with the homologous domains of DAF or MCP [121,123]. A recent study on DAF and MCP chimera showed that domains 1-2 (homologous domains in DAF are CCP 2-3) and 2-3 also serve as functional modules for DAA and CFA in these proteins [125]. It can, therefore, be concluded that vRCAs are true homologs of huRCA proteins.…”
Section: Structure-function Relationship Of Viral Rcamentioning
confidence: 69%
“…Fourth, regulatory determinants in RCAs are conserved evolutionarily. The 'functional blocks' for CFA and DAA in the vRCAs were shown to be conserved in the huRCAs too, and it led to the construction of a dual-activity human DAF-MCP chimera [125]. Besides, the functional motifs [139] and hotspots [118,123] are also evolutionarily conserved.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations